Research progress and prospect of Emeishan mantle plume metallogenic system - Liu, Zhicheng; Wen, Jun; Zhao, Wei; Chen, Min; Liu, Hong; Zheng, Mengtian; Tian, Ye; Guo, Yuheng (Frontiers in Earth Science, 2025)
The Emeishan Large Igneous Province (ELIP) in southwestern China, formed by the Emeishan mantle plume, hosts diverse mineralization systems. This study classifies deposits into two types: those directly and indirectly related to the plume. Directly related deposits (∼260 Ma) include magmatic Fe-Ti-V oxide and Cu-Ni-PGE sulfide deposits, and hydrothermal Nb-Ta-Zr-REE deposits, concentrated in the ELIP’s inner zone. Indirectly related deposits, such as weathering crust-type REE-Sc-Ti ores and Carlin-type gold deposits, formed post-ELIP through weathering, sedimentation, and hydrothermal processes, and are distributed in the middle-outer zones. Spatiotemporal analysis reveals that directly related deposits formed synchronously with ELIP magmatism, while indirectly related deposits exhibit dispersed ages from the Late Permian to Quaternary. The former originated from plume-driven magmatism, whereas the latter were influenced by thermal effects, ancient faults, and later geological processes. The study highlighted the plume’s role in global mineralization, proposing a resource effect law where mantle plumes enhance mineral and hydrocarbon formation. Comparative research with other Large Igneous Provinces is essential to address critical mineral shortages and ensure sustainable resource development.